2014
DOI: 10.1111/efp.12096
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of attack and defence in woody plant–Phytophthora interactions

Abstract: Summary This review comprises both well‐known and recently described Phytophthora species and concentrates on Phytophthora–woody plant interactions. First, comprehensive data on infection strategies are presented which were the basis for three models that explain invasion and spread of Phytophthora pathogens in different woody host plants. The first model describes infection of roots, the second concentrates on invasion of the trunk, and the last one summarizes infection and invasion of host plants via leaves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 185 publications
(343 reference statements)
5
99
0
9
Order By: Relevance
“…data). Further studies should therefore be carried out at different temperatures and with other techniques, such as fluorescence (Oßwald et al, 2014) and molecular methods (Bodles et al, 2006), to determine the damage caused beyond the visible symptoms. …”
Section: Effect Of Fusarium Mycoviruses On Pathogenicitymentioning
confidence: 99%
“…data). Further studies should therefore be carried out at different temperatures and with other techniques, such as fluorescence (Oßwald et al, 2014) and molecular methods (Bodles et al, 2006), to determine the damage caused beyond the visible symptoms. …”
Section: Effect Of Fusarium Mycoviruses On Pathogenicitymentioning
confidence: 99%
“…For example, most Phytophthora and a few Pythium species specifically secrete large amounts of elicitins, a group of unique highly conserved proteins whose molecular roles have been investigated and constitute a matter of debate (reviewed by Ponchet et al 1999;Oßwald et al 2014). Elicitins are able to facilitate infection (virulence factors), appear to be required for the colonization process, and are determinants for the aggressiveness of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Elicitins are able to facilitate infection (virulence factors), appear to be required for the colonization process, and are determinants for the aggressiveness of the pathogen. For instance, it was recently reported for the Q. suber-P. cinnamomi pathosystem using a β-cinnamomin (β-CIN) knock-down P. cinnamomi strain (Horta et al 2010) and shown for the role of citricolin from P. plurivora in the infection of beech roots (Oßwald et al 2014), and also suggested by the positive correlation of virulence with ram-a2 expression in P. ramorum (Manter et al 2010). Elicitins were shown to induce defence responses in plants (avirulence factors or elicitors) (Bonnet et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Essas duas isoflavonas são as mais investigadas para a especificidade na atração de zoósporos e são encontradas em concentrações elevadas nas sementes. Quando do processo de germinação do hospedeiro, a liberação dessas duas isoflavonas ocorre pelas raízes, na região da rizosfera (OßWALD et al, 2014;ZHU et al, 2005 A ação da corrente elétrica na motilidade de zoósporos também é outro tipo de taxia estudado, pois muitos zoósporos são atraídos eletrostaticamente para as diversas superfícies de potenciais plantas hospedeiras (TYLER, 2002). Os gradientes elétricos gerados pelas raízes das plantas na rizosfera são condições que influenciam na direção dos zoósporos, ora levando-os para perto ou para longe da superfície das raízes (MORRIS; REID; GOW, 1992).…”
Section: Considerações Sobre O Reconhecimento De Hospedeiros Por Estrunclassified